The Political Exploitation and Human (In) Security of Illegal Street Vendors in the Post-colonial Urban Informal Sector of Harare in Zimbabwe - Ndawana, Enock (Frontiers in Sustainable Cities, 2022)
This article examines the complexities around urban informality, in particular illegal street vending in post-colonial Harare in Zimbabwe from 2000 to 2021. It focuses on the positions of the ruling party, the Zimbabwe African National Union Patriotic Front and the Movement for Democratic Change opposition political party regarding illegal street vending. The study acknowledges the role played by the broader macro-economic environment in initiating and sustaining informal trading practices in the City of Harare but establishes the link between illegal street vending and politics and the concomitant effects on human security. Among others, it uses Ananya Roy's ideas about how the state “makes and unmakes” informality and primary and secondary sources of data to mainly argue that the political exploitation of the illegal street vending activities in Harare has detrimental effects on both urban governance and human security. The article concludes that illegal street vending is an integral part of urban societies in Africa and beyond serving different needs in the local economy. Consequently, the politicisation and human (in) security of the illegal street vendors in Harare can partly be mitigated when formal employment is generated and political parties stop interfering in the running of the city for the furtherance of their selfish agendas.